Respuesta :
Answer:
x = 1, -7/8
Step-by-step explanation:
Equation: 8w^2 - w 7 = 0
Factor: (x - 1)(8x + 7) = 0
Solve for 0: x - 1 + 1 = 0 + 1 -> x = 1
8x / 8 + 7 - 7 = 0 - 7 / 8 -> x = -7/8
Answer:
w = - [tex]\frac{7}{8}[/tex], w = 1
Step-by-step explanation:
Given
8w² - w - 7 = 0
Consider the factors of the product of the w² term and the constant term which sum to give the coefficient of the w- term.
product = 8 × - 7 = - 56 and sum = - 1
The factors are - 8 and + 7
Use these factors to split the w- term
8w² - 8w + 7w - 7 = 0 ( factor the first/second and third/fourth terms )
8w(w - 1) + 7(w - 1) ← factor out (w - 1) from each term
(w - 1)(8w + 7) = 0
Equate each factor to zero and solve for w
8w + 7 = 0 ⇒ 8w = - 7 ⇒ w = - [tex]\frac{7}{8}[/tex]
w - 1 = 0 ⇒ w = 1